Current Assessment and Determining the Opportunities for Application of MBT-CD.08 Technology for Domestic Solid Waste Treatment in Pleiku City - Hung, Nguyen Tri Quang; Toan, Dang Xuan; Ky, Nguyen Minh (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 2DO - 10.25073/2588-1094/vnuees.4224, 2018)
The purpose of the study was to evaluate the current situation and determining the opportunities for application of MBT-CD.08 technology for domestic solid waste treatment in Pleiku city. In period from 2012 to 2016, the total solid waste volume were 35,386; 38,689; 43,243; 46,900 and 50,737 tons per year in turn [1]. The results showed that the largest organic and combustible wastes were 62% and 22%, respectively. Researching results also showed that the currenttly waste treatment process due to water resource pollution which the caused unpleasant smell and decresed ecological beauty in Pleiku city. On average in Pleiku city, solid wastes landfill used a large land (25 ha) in period of 1998-2016 in context of the land use demands were increasing for different purposes. In addtion, results of the composition and volume from urban solid waste were relevant with the standards of MBT-CD.08 technology. The totally heating value of 139 tons domestic waste per day was 1,134.10 6 kJ and which was equal to the average value of 8.157,7 kJ/kg of waste. MBT-CD.08 technology showed the opportunities, benefits and advantages in the process of domestic solid waste treatment and environmental protection. Keywords: Solid waste, treatment, management, MBT-CD.08, technology, opportunity.